Aplikasi E-Soil untuk Mengidentifikasi Warna Tanah Berbasis Android Menggunakan Munsell Soil Color Chart - Chusyairi, Ahmad (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Agriculture in Singojuruh Subdistrict, Banyuwangi Regency, East Java Province has superior agriculture, namely: organic farming. Emphasis on organic farming is the treatment of soil in the fields, so that it has fertile identified nutrient content. The land in the rice field has a different color depending on the geographical conditions of the area, so that it affects the nutrient content of the soil. In an effort to make it easier for farmers to identify the color of the soil, an Android-based application is needed. The method used in the study is a qualitative approach and the Munsell Soil Color Chart color notation. The conclusion obtained in this study is that the E-Soil Application is used to assist farmers in identifying soil colors with an Android-based using the Munsell Soil Color Chart and can be accessed on Google Play with the search word E-Soil or URL link: https://play.google.com/store/apps/details?id=com.stikom.esoil.Â Kata kunci â€” E-Soil, Munsell Soil Color Chart, Singojuruh, Soil Color